Contact Lens Use in Patients With Boston Keratoprosthesis Type 1: Fitting, Management, and Complications. Issue 6 (November 2015) - Thomas, Merina; Shorter, Ellen; Joslin, Charlotte E.; McMahon, Timothy J.; Cortina, M. Soledad
Abstract : Abstract: The Boston type 1 keratoprosthesis (KPro) is the most commonly used artificial cornea worldwide. Long-term bandage contact lenses are the standard of care for patients with these devices. The goal of bandage contact lenses is to maintain hydration and to protect the corneal tissue that surrounds the anterior plate of the keratoprosthesis which is vulnerable to desiccation, epithelial breakdown, dellen formation, and corneal melt. Contact lenses can also improve comfort, correct refractive errors, and improve the cosmesis of patients with artificial corneas. However, the continuous use of contact lenses places these patients at risk for complications such as lens loss, lens deposits, chronic conjunctivitis, and infection. In addition, obtaining an adequate fit in a patient with a compromised ocular surface and history of multiple surgeries including glaucoma drainage devices can present a challenge. This review discusses the types of contact lenses used, special fitting considerations, and common complications in patients with previous KPro surgery.